Finding bedrock in uncontrolled clayey fill - success with GPR profiling. Issue 1 (1st December 2016) - Danis, Cara; Lawrence, Roderick
Abstract : GPR in clay rich environments is often assumed to yield poor results due to signal attenuation, however it can still be possible to penetrate deep enough to reflect off targets of interest. Finding the bedrock level in an old quarry filled with clay and building rubble was successful using GPR reflection image profiling primarily due to the fact the fill material had previously been dewatered. Distinctive layers were observed in the fill material which when drilled corresponded to specific dominant material types. It appears the compaction level of the clay and the moisture content of the fill were important factors in the success of the GPR profile.